Antibacterial and Antioxidant Activity of Biosynthesized Silver Nanoparticles Produced by Aegle marmelos Fruit Peel Extract. Issue 3 (4th May 2019) - Kushwah, Mamta; Bhadauria, Seema; Singh, K. P.; Gaur, M.S.
Abstract: In this work 1 mL, 5 mL and 10 mL of fruit peel extract were used in biosynthesis of AgNPs (a), (b) and (c), respectively . Phytochemical analyses of fruit peel extract demonstrated the presence of reducing agent such as steroids, flavonoids, polyphenolics, tannis, reducing sugar and amino acid compound. These compounds are confirmed by GC-MS analysis. Biosynthesized AgNPs were characterized by UV-Vis Spectra, Transmission Electron Microscopy (TEM), Selected Area Electron Diffraction (SAED), Fourier Transform Infrared Spectroscopy (FT-IR), and Zeta Potential. Biosynthesized AgNPs were shows an antibacterial property against gram negative Escherichia coli and antioxidant property. The higher value of zone inhibition observed by 12.5 μg/mL of AgNPs synthesized with 10 mL of A.marmelos (L) have been observed to be 24 ± 0.9 mm. Bio-synthesized AgNPs (c) shows high antioxidant and antibacterial potency because of their monodisperse nature.